Birnessite films are sensitive indicators of microbial manganese reduction in soil. Issue 1 (13th November 2022) - Hino, Katelyn C.; Romero, Jasper; Loffredo, Joseph L.; Stolt, Mark; Amador, Jose; Moseman‐Valtierra, Serena; Wigand, Cathleen; Pellock, Brett J.
Abstract: Manganese (Mn) and Fe indicator of reduction in soils (IRIS) devices are low‐cost, convenient tools for identifying reducing conditions in soils. Because Mn is reduced at similar redox potentials as nitrate, there is considerable interest in using Mn IRIS tools for understanding microbial reduction of Mn as a surrogate for processes such as denitrification. However, the sensitivity of these devices to differences in Mn‐reducing capacity has not been empirically investigated. Here we have found that the rate of birnessite paint removal from Mn IRIS films exposed to a twofold dilution series of the Mn‐reducing bacterium Shewanella oneidensis is directly proportional to the number of S. oneidensis cells added. Thus, regularly monitored birnessite IRIS sensors are capable of indicating twofold differences in Mn reduction in soil and can be used to measure relative Mn reduction rates over time in a single location or compare and contrast Mn reduction rates across soil types. Core Ideas: Manganese indicator of reduction in soils film sensitivity was determined using a Shewanella oneidensis dilution series. Manganese indicator of reduction in soils films are sensitive tools for measuring Mn reduction rates in soil. Timing of Mn indicator of reduction in soils film deployment and observation is critical for maximum sensitivity.